Interculturalism in The Eyes of Marege Performance - Alif Anggara (Institut Seni Indonesia Yogyakarta, 2018)
AbstractThe Eyes of Marege is a surreal drama which consists of two acts with fourteen scenes. It is an intercultural performance that raises the history of relations between Makassar and Aborigines in the past. The research aims to know the basic idea of creation, the concretization stages, as well as the structure and texture of the performance. This research applies a qualitative method with a sociological approach. Observations were started from DVDs of the performance and drama script of The Eyes of Marege. Data were collected from interviews with some respondents and literature study. The Eyes of Marege is inspired by folklore, myths, songs about Makassarese coming to Arnhem Land - Northern Australia to find sea cucumbers. It was the place where Julie Janson had lived for thirty years and was raised by the Yolngu family. In addition, Julie Janson got some other inspirations from several readings and personal experiences when visiting Makassar.Keywords: Eyes of Marege; Makasarese folklore; Julie JansonAbstrakInterkuluralisme dalam Pertunjukan The Eyes of Marege. The Eyes Of Marege merupakan drama absurd atau surealis yang terdiri dari dua babak dengan empat belas adegan. Penelitian ini bertujuan untuk mengetahui ide dasar penciptaan, tahapan konkretisasi, serta struktur maupun tekstur pertunjukannya. Penelitian ini menggunakan metode kualitatif dengan pendekatan sosiologi. Penelitian dilakukan dengan cara pengamatan pertunjukan dan analisis naskah drama diikuti dengan wawancara dan studi pustaka. Berdasarkan penelitian dapat disimpulkan bahwa drama ini terinspirasi dari cerita rakyat, mitos, nyanyian-nyanyian tentang orang Makassar yang datang ke Arhemland – Australia Utara untuk mencari teripang. Tempat itu adalah tempat di mana Julie Janson pernah tinggal selama tiga puluh tahun dan diasuh oleh keluarga Yolngu. Drama ini dapat digolongkan sebagai pertunjukan interkultural yang mengangkat masalah sejarah hubungan antara suku Makassar dan suku Aborigin yang pernah terjalin di masa silam.Kata kunci: Eyes of Marege; folklore Makassar; Julie Janson